Numerical and Mechanical Analysis of Direct Wafer Bonding Considering Non-Uniform Impurity Particle Distributions - Feixiang Tang; Siyu He; Yuhan Li; wenjin Liu; Fang Dong; Sheng Liu (Microsystems & Nanoengineering)
Abstract Direct wafer bonding allows polished semiconductor wafers to be joined together without the use of a binder. It has a wide range of applications in integrated circuit fabrication, micro-electro-mechanical systems (MEMS) packaging and multifunctional chip integration. Chip deflection and strain energy can be used to assess the bonding quality, and impurities have an important effect on the bonding quality. In this paper, a mathematical model and a finite element model of wafer bonding are established. The effects of different impurity distributions (Cluster, Complex, Face, Line) on the bonding quality of wafers are investigated, and the results show that the curvature and thickness of the wafer as well as the distribution of the impurity particles jointly determine the strain energy of the wafer under a certain pressure. Among them, the impurity particle surface distribution has the greatest influence on the wafer bonding quality. Finite element simulations verified the correctness of the proposed model. This work provides a theoretical basis for studying the effect of impurity distribution on wafer bonding performance.